Out of sight, Out of mind — but not Out of scope: the need to consider ozone (O3) in restoration science, policy, and practice. Issue 7 (19th April 2022) - Perring, Michael P.; Bullock, James M.; Alison, Jamie; Holder, Amanda J.; Hayes, Felicity
Abstract : Restoration ecologists have local‐ to global‐scale ambitions in a policy framework of sustainable development goals and reversing biodiversity loss. Emphasis is given to environmental alteration, typically considering land degradation and climate change. Other related environmental drivers, such as pollution, receive less attention. Here we emphasize that terrestrial restoration discourse needs to consider tropospheric ozone (O3 ) pollution. O3 's pervasive influence on plants and other ecosystem components provides for the possibility of consequences at community and ecosystem levels. The precursor chemicals that lead to O3 formation are increasing, precipitously so in rapidly industrializing regions of the world. Yet, a review of critical restoration guidance and journals suggests that because O3 is out of sight, it remains out of mind. Based on a narrative cross‐discipline literature review, we examine: (1) How O3 could affect the achievement of restoration goals and (2) How restoration interventions could feedback on tropospheric O3 . Evidence, currently limited, suggests that O3 could impair the achievement of restoration goals to as great an extent as other drivers, but, in general, we lack direct quantification. Restoration interventions (e.g. tree planting) that may be considered successful can actually exacerbate O3 pollution with negative consequences for food security and human health. These wide‐ranging effects, across multiple goals, mean that O3 is not out of scope for restoration science, policy, and practice. In detailing a strategic ozone‐aware restoration agenda, we suggest how restoration science and policy can quantify O3 's influence, while outlining steps practitioners can take to adapt to/mitigate the impacts of O3 pollution.